Modulation of thermoelectric power generation performance of ZnO nanostructures by controlling the Mn atoms concentration. Issue 11 (1st June 2022) - Rehman, Ubaid ur; Jacob, Jolly; Al-Harbi, F.F.; Ashfaq, A.; Mahmood, K.; Ali, A.; Amin, N.; Amami, Mongi; Hussain, S.; Javaid, K.; Ikram, Salma; Sahar, Kashaf ul
Abstract: In the present study, the thermoelectric power generation performance of ZnO nanostructures is improved by controlling the Mn doping concentration. For this purpose, Mn doped ZnO nanostructures (x = 0.1, 0.2, 0.3, 0.4& 0.5) were fabricated by a simple hydrothermal route and their structural, morphological and thermoelectric properties were investigated. For thermoelectric behavior, Seebeck and Hall measurements were performed. Seebeck data exhibits the improvement in the Seebeck coefficient value from 8.5 to 57 ± 0.1 μV/ ° C with the increase in Mn concentration. This enhancement in Seebeck coefficient was related to the energy filtering effect due to the presence of MnO2 based secondary phases. On contrary, the electrical conductivity data represent the inverse behavior (56-31.5 ± 0.1 S/cm) in response to the Mn doping concentration. The overall highest Seebeck value obtained for the sample doped at x = 0.5 leads to the highest thermoelectric power factor value up to 1.023 × 10 -5 Wm -1 C -2 . To support our argument, we have performed supplementary measurements such as X-Ray Diffraction and scanning electron microscopy which confirm the presence of mixed-phase composites. Highlights: Mn doped ZnO nanostructures were fabricated via simple hydrothermal route. X-ray diffraction data confirms the formation of mixed phases of ZnO/MnO2 . Seebeck coefficient was improved with the increase in Mn doping concentration. Highest power factor (1.023 × 10 -5 Wm -1 C -2 )was achieved for x = 0.5 doping concentration.